Pengenalan Aplikasi Elektronika Berbasis Android di Madrasah Aliyah Negeri 1 (MAN) Grobogan - Utari Utari; Nuryani Nuryani; Riyatun Riyatun; Budi Purnama (SEMAR (Jurnal Ilmu Pengetahuan, Teknologi, dan Seni bagi Masyarakat), 2024)
AbstractThe rapid development of science and technology in recent years has greatly affected the teaching and learning process, especially physics lessons in high school. One of the technology products that has been widely used in all levels of society, including by students both at the elementary level to universities, is the smartphone. This community service activity is intended to increase the knowledge and skills of high school students in using smartphones with the Android operating system in a more effective, interactive, and fun learning process. This activity is carried out through training with theoretical presentation methods, practice, and discussion (question and answer). Direct practice is carried out using electronic media in smartphones owned by each participant (student). The practice used Android to create simple programs with the koltin programming language. Kotlin programming language was chosen because it is simpler, safer, and more productive than other programming languages, especially in the context of Android application development. From the discussion at the end of the training, it was concluded that students' knowledge and interest related to Android applications in learning are increasing because learning is done with easy, interactive, and fun methods. In addition, there is a growing interest of the students to continue their studies in college, especially in S1 Physics FMIPA UNS.    Keywords: Android, Kotlin, Learning, Student Univer